The unusual normal state and charge-density-wave order in 2H-NbSe2. (16th April 2015) - Koley, S; Mohanta, N; Taraphder, A
Abstract: Competition between collective states like charge-density-wave and superconductivity, unencumbered by the spin degrees of freedom, is played out in some of the transition metal dichalcogenides. Although 2H-NbSe2 has received much less attention than some of the other members of the family (such as 1T-TiSe2 and 2H-TaSe2 ) of late, it shows superconductivity at 7.2 K and incommensurate charge ordering at 33 K. Recent experiments, notably angle resolved photoemission spectroscopy, have cast serious doubts on the theories based on Fermi surface nesting and electron–phonon interaction. The normal state has been found to be a poor, incoherent metal and remarkably, the coherence increases in the broken symmetry state. From a preformed excitonic liquid scenario, we show that there exists a natural understanding of the experimental data on 2H-NbSe2, based on electron–electron interaction. The collective instabilities, in this scenario, are viewed as a condensation of an incoherent excitonic liquid already present at high temperature.